High-performance titanium-based composite material based on additive manufacturing and preparation method thereof

Through the TiB reinforcement generated by uniform dispersion in the titanium alloy matrix, the problem of insufficient hardness and wear resistance of titanium alloy materials is solved, and the preparation of high-performance titanium-based composite materials is realized, with excellent mechanical properties and forming characteristics.

CN119426613APending Publication Date: 2025-02-14CISDI RES & DEV CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411538542.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Titanium alloy materials have low hardness and poor wear resistance. The addition of reinforced phases will cause a sharp decline in the plasticity of the titanium-based composite materials, and even brittle fracture during the forming process.

Method used

TiB was produced by TiB in the titanium-coated reinforced phase nanoparticles, and uniformly dispersed in the titanium alloy matrix through selective laser melting technology to prepare a high-performance titanium-based composite material.

Benefits of technology

The density and fine crystal strengthening of titanium-based composite materials have been achieved, the hardness can reach 477.46HV, the tensile strength can exceed 1350MPa, and the material is well formed, and is suitable for aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426613A_ABST
    Figure CN119426613A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of titanium alloy materials and additive manufacturing, and relates to a high-performance titanium-based composite material based on additive manufacturing and a preparation method of the high-performance titanium-based composite material. The preparation method comprises the following steps that titanium alloy powder subjected to vacuum drying treatment and titanium-coated reinforced phase nanoparticles are added into a ball mill to be subjected to ball milling treatment in the inert gas atmosphere, and evenly-mixed composite powder is obtained; and after the composite powder in the first step is subjected to vacuum drying, the composite powder is evenly laid on a forming base plate through additive manufacturing equipment, the composite powder is molten layer by layer through a heat source, and the high-performance titanium-based composite material is obtained after solidification. According to the titanium-based composite material and the preparation method thereof, TiB generated by the in-situ reaction of the B element in the titanium-coated reinforced phase nanoparticles and the Ti element in selective laser melting forming is adopted, the TiB is uniformly dispersed and distributed in a titanium alloy matrix, the prepared titanium-based composite material has good density, the strength, hardness and other properties of the material are obviously improved, and the comprehensive mechanical property is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of titanium alloy materials and additive manufacturing, and relates to a high-performance titanium-based composite material based on additive manufacturing and a preparation method thereof. Background Art

[0002] With the acceleration of the global industrialization process and the rapid development of industries such as aerospace, automobiles and ships, and biomedicine, the demand for high-performance materials is growing. Titanium alloy, as a high-performance metal material, has the characteristics of high strength, low density, excellent corrosion resistance and heat resistance, and has shown extensive application potential and important strategic value in multiple industrial fields. At the technical level, the production and processing technology of titanium alloys is also constantly improving. At present, traditional smelting and casting technologies are relatively mature, while emerging additive manufacturing technologies have further improved the performance and processing efficiency of titanium alloys. Selective laser melting technology is an advanced forming technology that has emerged and developed rapidly in recent years. It directly melts titanium alloy powder through a laser beam and accumulates layer by layer to form three-dimensional solid parts. It has the advantages of high precision, high flexibility and high material utilization, and can produce complex shapes and high-performance titanium alloy parts to meet the needs of aerospace, medical and other fields for high-performance materials.

[0003] However, titanium alloys still have some shortcomings that cannot be ignored. They have low hardness and poor wear resistance, and face many challenges in high-performance applications. Titanium-based composites are a new type of material made of titanium or titanium alloy as a matrix, and are made by adding polymer materials, fibers, inorganic non-metallic reinforcements, etc., which combine the high strength and toughness of the titanium alloy matrix with the high strength characteristics of the ceramic phase. There are many options for reinforcements suitable for titanium alloy matrices. Among them, TiB reinforcements have excellent mechanical properties and density and thermal expansion coefficients close to those of titanium, making them one of the ideal reinforcements for titanium-based composites. However, the addition of reinforcement phases will cause a sharp drop in the plasticity of titanium-based composites, and even brittle fracture during the forming process. To avoid this problem, the optimization of the forming process and the design of the microstructure morphology of titanium-based composites are currently hot issues that are widely studied. Summary of the invention

[0004] In view of this, an object of the present invention is to provide a high-performance titanium-based composite material based on additive manufacturing and a preparation method thereof, so as to solve the problems raised in the background technology.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high-performance titanium-based composite material based on additive manufacturing comprises the following steps:

[0007] Step 1. preparing composite powder: adding vacuum dried titanium alloy powder and titanium-coated reinforcement phase nanoparticles into a ball mill and performing ball milling treatment under an inert gas atmosphere to obtain a uniformly mixed composite powder;

[0008] Step 2. Additive manufacturing: After the composite powder in step 1 is vacuum dried, the composite powder is evenly spread on the forming substrate through additive manufacturing equipment, and the composite powder is melted layer by layer through a heat source to obtain a high-performance titanium-based composite material after solidification.

[0009] Furthermore, in step 1, the mass fractions of the components of the composite powder are as follows: 95% to 99% of the titanium alloy powder and 1% to 5% of the titanium-coated reinforcing phase nanoparticles.

[0010] Furthermore, the titanium alloy powder includes one or more combinations of pure titanium, TC4, TA11 and TA15, and the particle size of the titanium alloy powder ranges from 15 to 53 μm.

[0011] Furthermore, in the step 1, the vacuum drying treatment is as follows: placing the titanium alloy powder and the titanium-coated reinforcement phase nanoparticles in stainless steel trays respectively, and keeping them in a vacuum environment at 100 to 120° C. for 1 to 2 hours;

[0012] In the ball milling process, a grinding ball with a diameter of 5 mm was selected, the ball-to-material ratio was 1:2, the ball mill speed was 100-200 rpm, the ball milling time was 4-8 h, and the ball milling atmosphere was an argon atmosphere.

[0013] Furthermore, in step 2, the vacuum drying temperature is 100-120° C. and is kept warm for 3-5 hours.

[0014] Further, the additive manufacturing equipment is a selective laser melting equipment, and argon gas is introduced into the selective laser melting equipment to fill the printing chamber to keep the oxygen content in the printing chamber below 100 ppm, and the formed substrate is a TC4 substrate;

[0015] The process parameters of the selective laser melting equipment are: laser spot diameter is 80μm, laser power is 100-300W, scanning speed is 300-1000mm / s, scanning spacing is 50-100μm, powder layer thickness is 20-60μm, and forming substrate preheating temperature is 160-200℃.

[0016] Furthermore, in step 1, the method for preparing the titanium-coated reinforcing phase nanoparticles comprises the following steps:

[0017] Step a. ball-milling titanium powder and reinforcing phase particles to obtain a uniform mixed powder, wherein the particle size of the titanium powder is 20 to 200 μm, the particle size of the reinforcing phase particles is 10 to 100 μm, the mass fraction of the titanium powder in the mixed powder is 15 to 50%, and the rest is reinforcing phase particles;

[0018] Step b. preparing the mixed powder into a titanium-coated reinforcing phase powder by a high-frequency induction plasma method; specifically, an inert gas is filled into a vacuum reaction chamber, and the mixed powder is fed into a plasma torch with the inert gas, and after a thermal plasma reaction, it is rapidly cooled to obtain a titanium-coated reinforcing phase powder;

[0019] Step c. Screening titanium-coated reinforcing phase powder with a particle size of less than 1 μm as titanium-coated reinforcing phase nanoparticles.

[0020] Furthermore, the reinforcing phase particles include one or more combinations of B powder, LaB6 and B4C.

[0021] Furthermore, in step b, the preparation of titanium-coated reinforcement phase powder by high-frequency induction plasma method is carried out in a vacuum reaction chamber, and an inert gas is filled in the vacuum reaction chamber so that the air pressure value of the vacuum reaction chamber is between 0.01 and 0.03 MPa, and the mixed powder is sent into the vacuum reaction chamber at a speed of 3 to 20 m / s under the action of the inert gas.

[0022] A high-performance titanium-based composite material based on additive manufacturing, wherein the high-performance titanium-based composite material is a high-performance titanium-based composite material prepared by the preparation method of the high-performance titanium-based composite material based on additive manufacturing.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention uses TiB generated by in-situ reaction of B element in titanium-coated reinforcing phase nanoparticles with Ti element during selective laser melting, and evenly disperses it in the titanium alloy matrix. The prepared titanium-based composite material has good density, and realizes fine grain strengthening and dispersion strengthening. The hardness can reach 477.46HV, and the tensile strength can exceed 1350MPa.

[0025] 2. The present invention adopts selective laser melting technology to prepare high-performance titanium-based composite materials. Compared with traditional processing technology, it can achieve near-net forming of parts and can prepare titanium alloy parts with complex shapes and fine structural scales, meeting the needs of high-performance materials in aerospace and other fields.

[0026] 3. Compared with ordinary reinforcing phase nanoparticles, the titanium-coated reinforcing phase nanoparticles provided by the present invention have better interface bonding ability with the titanium alloy matrix, are easier to disperse in the molten pool, have good stability, and can be widely used in the forming of titanium alloys; secondly, the high-performance titanium-based composite material forming specimen has no cracks, a relatively smooth surface, a high degree of densification, and the strength, hardness and other properties of the material are significantly improved, and the comprehensive mechanical properties are excellent, which has good application prospects in the fields of aerospace, automobiles, ships, and biomedicine.

[0027] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0029] Figure 1 The scanning electron microscope images are of pure TC4 metal powder (a) and the composite powder of TC4 and titanium-coated reinforcing phase nanoparticles after ball milling in Example 1 (b);

[0030] Figure 2 This is a macroscopic morphology of the titanium-based composite material block sample prepared in Example 1;

[0031] Figure 3 The microstructure scanning electron microscope images of the titanium alloy material (ab) prepared in Comparative Example 1 and the titanium-based composite material (cd) prepared in Example 2 are shown. DETAILED DESCRIPTION

[0032] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0033] Among them, the drawings are only used for illustrative explanations, and they only represent schematic diagrams rather than actual pictures, and should not be understood as limitations on the present invention. In order to better illustrate the embodiments of the present invention, some parts of the drawings may be omitted, enlarged or reduced, and do not represent the size of actual products. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.

[0034] The same or similar numbers in the drawings of the embodiments of the present invention correspond to the same or similar parts; in the description of the present invention, it should be understood that if the terms "upper", "lower", "left", "right", "front", "rear", etc. indicate the orientation or position relationship, they are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the terms describing the position relationship in the drawings are only used for illustrative purposes and cannot be understood as limiting the present invention. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0035] The present invention provides a method for preparing a high-performance titanium-based composite material based on additive manufacturing. The preparation process is carried out in a high-frequency induction plasma device and an additive manufacturing device. The specific preparation process is as follows:

[0036] Step 1. Preparation of titanium-coated reinforcement phase nanoparticles by high-frequency induction plasma method:

[0037] (1) putting titanium powder with a purity of 99.9% and a particle size of 20 to 200 μm and reinforcing phase particles with a purity of 99.9% and a particle size of 10 to 100 μm into a ball mill, and ball milling at a speed of 100 rpm for 12 hours to obtain a mixed powder, wherein the mass fraction of the titanium powder in the mixed powder is 15 to 50%, and the rest is reinforcing phase particles;

[0038] (2) In a vacuum reaction chamber for preparing titanium-coated reinforcing phase powder, an inert gas is filled and the gas pressure is kept at 0.01-0.03 MPa. A high-frequency induction plasma generator is operated. Under the action of a high-frequency power supply, the working gas is ionized to form a high-temperature discharge area (with a plasma torch). The mixed powder is sprayed into the plasma torch at a speed of 3-20 m / s with an inert gas. The mixed powder absorbs a large amount of heat in the high-temperature plasma in the plasma torch, and the surface melts rapidly. The mixed powder enters the reactor at an extremely high speed and is rapidly cooled by gas heat exchange. The mixed powder cools and solidifies to grow into ultrafine particle clusters, which are collected in a collecting chamber. Since the reinforcing phase has a higher melting point, it will preferentially nucleate and solidify, while titanium has a lower melting point and will nucleate on the surface of the solidified reinforcing phase, thereby achieving titanium coating on the reinforcing phase particles, thereby obtaining titanium-coated reinforcing phase powder. Specifically, a high-frequency induction plasma nanopowder preparation device can be used to prepare titanium-coated reinforcing phase powder.

[0039] (3) screening titanium-coated reinforcement phase powder with a particle size of less than 1 μm as a finished product of titanium-coated reinforcement phase nanoparticles;

[0040] Step 2. Preparation of titanium alloy and titanium-coated reinforced phase nanoparticle composite powder:

[0041] (1) placing titanium alloy powder and titanium-coated reinforcing phase nanoparticles in a stainless steel tray respectively, and keeping the temperature at 100-120° C. for 1-2 hours in a vacuum environment; the mass fraction of each component of the titanium alloy and titanium-coated reinforcing phase nanoparticle composite powder is: titanium alloy powder is 95%-99%, and titanium-coated reinforcing phase nanoparticles is 1%-5%; wherein the titanium alloy powder is a spherical powder with a particle size distribution of 15-53 μm;

[0042] (2) The titanium alloy and titanium-coated reinforcing phase nanoparticle composite powders were ball milled in an inert gas atmosphere, the selected grinding balls had a diameter of 5 mm, the ball-to-material ratio was 1:2, the ball mill speed was 100-200 rpm, and the ball milling time was 4-8 h;

[0043] Step 3. Additive manufacturing of high-performance titanium-based composites;

[0044] (1) vacuum drying the titanium alloy and titanium-coated reinforcing phase nanoparticle composite powder obtained in step 2 at a vacuum drying temperature of 100 to 120° C. for 3 to 5 hours;

[0045] (2) The dried titanium alloy and titanium-coated reinforced phase nanoparticle composite powder are placed in the powder cylinder of the additive manufacturing equipment, and the powder spreading equipment evenly spreads the titanium alloy and titanium-coated reinforced phase nanoparticle composite powder on the forming substrate, melts the composite powder layer by layer through a heat source, and obtains a block sample after solidification; the additive manufacturing equipment is a selective laser melting equipment; the forming substrate is a TC4 substrate; the process parameters of the selective laser melting forming are: laser spot diameter is 80μm, laser power is 100-300W, scanning speed is 300-1000mm / s, scanning spacing is 50-100μm, powder layer thickness is 20-60μm, and substrate preheating temperature is 160-200℃; before additive manufacturing, argon gas is introduced into the selective laser melting equipment to fill the printing chamber to keep the oxygen content in the printing chamber below 100ppm;

[0046] (3) The block sample is cut from the substrate using a wire cutting process to obtain a high-performance titanium-based composite material component based on additive manufacturing.

[0047] Example 1

[0048] A method for preparing a high-performance titanium-based composite material based on additive manufacturing comprises the following steps:

[0049] (i) Preparation of titanium-coated reinforcement phase nanoparticles by high-frequency induction plasma method;

[0050] (1) Titanium powder with a purity of 99.9% and a particle size of 20 to 200 μm and B powder with a purity of 99.9% and a particle size of 10 to 100 μm are placed in a ball mill and ball milled at a speed of 100 rpm for 12 h to obtain a mixed powder; in the mixed powder, the mass fraction of titanium powder is 30%, and the rest is B powder.

[0051] (2) Inert gas is filled into the vacuum reaction chamber to keep the gas pressure at 0.01 MPa, and the plasma device is operated. Under the action of the high-frequency power supply, the working gas is ionized to form a high-temperature discharge area. The mixed powder is sprayed into the plasma torch at a speed of 20 m / s with inert gas. The mixed powder absorbs a large amount of heat in the high-temperature plasma, and the surface melts rapidly. It enters the reactor at an extremely high speed and is rapidly cooled by gas heat exchange. It cools and solidifies to grow into ultrafine particle clusters, which are collected in the collecting chamber. Since the melting point of the reinforcing phase is higher, it will preferentially nucleate and solidify, while titanium has a lower melting point and will nucleate on the surface of the solidified reinforcing phase, thereby realizing the coating of titanium on B powder.

[0052] (3) Screening titanium-coated reinforcing phase powder with a particle size of less than 1 μm as a finished product of titanium-coated reinforcing phase nanoparticles.

[0053] (ii) preparing composite powders of titanium alloy and titanium-coated reinforcement phase nanoparticles;

[0054] (1) TC4 powder and titanium-coated reinforcing phase nanoparticles were placed in stainless steel trays respectively and kept at 100°C for 2 h in a vacuum environment; the mass fractions of the components of the composite powder were: titanium alloy powder was 98%, and titanium-coated reinforcing phase nanoparticles were 2%; the titanium alloy powder was spherical powder with a particle size distribution of 15-53 μm.

[0055] (2) The selected grinding ball diameter is 5 mm, the ball-to-material ratio is 1:2, the ball mill speed is 200 rpm, and the ball milling time is 6 h.

[0056] (iii) Additive manufacturing of high-performance titanium-based composites;

[0057] (1) The composite powder obtained in step 1 is vacuum dried at a vacuum drying temperature of 100° C. for 5 h.

[0058] (2) The dried composite powder is placed in the powder cylinder of the additive manufacturing equipment, and the powder spreading equipment evenly spreads the composite powder on the forming substrate. The composite powder is melted layer by layer by a heat source, and a block sample is obtained after solidification. The additive manufacturing equipment is a selective laser melting equipment. The forming substrate is a TC4 substrate. The process parameters of the selective laser melting forming are: laser spot diameter is 80μm, laser power is 200W, scanning speed is 1000mm / s, scanning spacing is 75μm, powder layer thickness is 30μm, and substrate preheating temperature is 180℃.

[0059] (3) The block sample is cut from the substrate using a wire cutting process to obtain a high-performance titanium-based composite material component.

[0060] Figure 1 The scanning electron microscope images are of pure TC4 metal powder (a) and the composite powder (b) after ball milling of TC4 and titanium-coated reinforcing phase nanoparticles in Example 1. It can be seen that ball milling has almost no effect on the particle size of the composite powder, the sphericity and symmetry of the powder are well maintained, the titanium-coated reinforcing phase nanoparticles are evenly distributed on the surface of the spherical TC4 powder, no obvious adsorption agglomeration phenomenon is observed, and the composite powder still has good fluidity.

[0061] Figure 2 This is the macroscopic morphology of the titanium-based composite material block sample prepared in Example 1. No defects such as pores and cracks visible to the naked eye were observed on the surface of the sample, and the formability was good.

[0062] Example 2

[0063] A method for preparing a high-performance titanium-based composite material based on additive manufacturing comprises the following steps:

[0064] (i) Preparation of titanium-coated reinforcement phase nanoparticles by high-frequency induction plasma method;

[0065] (1) Titanium powder with a purity of 99.9% and a particle size of 20 to 200 μm and LaB6 powder with a purity of 99.9% and a particle size of 10 to 100 μm are placed in a ball mill and ball milled at a speed of 100 rpm for 12 h to obtain a mixed powder; in the mixed powder, the mass fraction of titanium powder is 50%, and the rest is LaB6 powder.

[0066] (2) Inert gas is filled into the vacuum reaction chamber to keep the gas pressure at 0.01 MPa, and the plasma device is operated. Under the action of high-frequency power, the working gas is ionized to form a high-temperature discharge area. The mixed powder is sprayed into the plasma torch at a speed of 20 m / s with inert gas. The mixed powder absorbs a large amount of heat in the high-temperature plasma, and the surface melts rapidly. It enters the reactor at an extremely high speed and is rapidly cooled by gas heat exchange. It cools and solidifies to grow into ultrafine particle clusters, which are collected in the collecting chamber. Since the melting point of the reinforcing phase is higher, it will preferentially nucleate and solidify, while titanium has a lower melting point and will nucleate on the surface of the solidified reinforcing phase, thereby realizing the titanium coating of LaB6 powder.

[0067] (3) Screening titanium-coated reinforcing phase powder with a particle size of less than 1 μm as a finished product of titanium-coated reinforcing phase nanoparticles.

[0068] (ii) preparing composite powders of titanium alloy and titanium-coated reinforcement phase nanoparticles;

[0069] (1) TC4 powder and titanium-coated reinforcing phase nanoparticles were placed in stainless steel trays respectively and kept at 100°C for 2 h in a vacuum environment; the mass fractions of the components of the composite powder were: titanium alloy powder was 96%, and titanium-coated reinforcing phase nanoparticles were 4%; the titanium alloy powder was spherical powder with a particle size distribution of 15-53 μm.

[0070] (2) The selected grinding ball diameter is 5 mm, the ball-to-material ratio is 1:2, the ball mill speed is 200 rpm, and the ball milling time is 6 h.

[0071] (iii) Additive manufacturing of high-performance titanium-based composites;

[0072] (1) The composite powder obtained in step 1 is vacuum dried at a vacuum drying temperature of 100° C. for 5 h.

[0073] (2) The dried composite powder is placed in the powder cylinder of the additive manufacturing equipment. The powder spreading equipment evenly spreads the composite powder on the forming substrate. The composite powder is melted layer by layer by a heat source, and a block sample is obtained after solidification. The additive manufacturing equipment is a selective laser melting equipment. The forming substrate is a TC4 substrate. The process parameters of the selective laser melting forming are: laser spot diameter is 80μm, laser power is 250W, scanning speed is 800mm / s, scanning spacing is 60μm, powder layer thickness is 30μm, and substrate preheating temperature is 200℃.

[0074] (3) The block sample is cut from the substrate using a wire cutting process to obtain a high-performance titanium-based composite material component.

[0075] Comparative Example 1

[0076] A titanium alloy material was prepared by the same method as in Example 1, except that titanium-coated reinforcing phase nanoparticles were not added.

[0077] Figure 3 The microstructure scanning electron microscope images of the titanium alloy material prepared in Comparative Example 1 and the titanium-based composite material prepared in Example 1. Columnar crystal phases were observed in the microstructure of the titanium alloy material, and a large number of elongated needle-shaped martensite existed in the crystals. In contrast, the matrix grains of the titanium-based composite material were significantly refined and were in a more fine lamellar shape. This is because TiB generated by the in-situ reaction of Ti and B during the forming process is dispersed in the titanium alloy matrix, preventing the growth of the matrix grains. TiB is in the form of nanoscale whiskers or irregular particles, and a large number of single whiskers gather together to form whisker clusters.

[0078] Table 1 shows the performance data of the titanium-based composite materials of Examples 1-2 and the titanium alloy material of Comparative Example 1.

[0079] Block specimen Density Hardness (HV) Tensile strength(MPa) Elongation(%) Example 1 99.78% 442.13 1277.67 6.62 Example 2 99.37% 477.46 1353.27 3.79 Comparative Example 1 99.91% 374.48 1009.56 11.74

[0080] As can be seen from the above table, the high-performance titanium-based composite materials prepared by the preparation method of the present invention in Examples 1 to 2 have a density higher than 99%, indicating that they have good formability. In terms of hardness, as the content of B element in the sample increases, the hardness of the titanium-based composite material gradually increases, and compared with ordinary titanium alloy materials, the hardness can be increased by up to 27.50%. This is because TiB itself has extremely high hardness, and the grain refinement of the titanium alloy matrix causes a hardening effect, which makes the titanium-based composite material have a higher hardness. In addition, the strengthening effect of TiB on the mechanical properties of the titanium-based composite material is also more obvious, and its tensile strength is higher than that of the titanium alloy material. Since many nano-scale TiB are dispersed in the titanium-based composite material, and the shear stress required for dislocations to bypass these dispersed phases gradually changes with the scale and uniformity of these whiskers, it shows higher strength. At the same time, due to the grain refinement of TiB, the titanium-based composite material will produce more grain boundaries than the titanium alloy, so that the dislocation movement during the stretching process is hindered, which also further improves the strength of the material. However, while TiB improves the strength, it also significantly deteriorates the plasticity of the titanium-based composite material, so that too high a TiB content will lead to a sharp decrease in the plasticity of the titanium-based composite material, and thus has little effect on improving its strength, as shown in Example 2.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a high-performance titanium-based composite material based on additive manufacturing, characterized in that: The following steps are involved: Step 1. preparing composite powder: adding vacuum dried titanium alloy powder and titanium-coated reinforcement phase nanoparticles into a ball mill and performing ball milling treatment under an inert gas atmosphere to obtain a uniformly mixed composite powder; Step 2. Additive manufacturing: After the composite powder in step 1 is vacuum dried, the composite powder is evenly spread on the forming substrate through additive manufacturing equipment, and the composite powder is melted layer by layer through a heat source to obtain a high-performance titanium-based composite material after solidification.

2. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 1, characterized in that: In step 1, the mass fractions of the components of the composite powder are: 95% to 99% of the titanium alloy powder and 1% to 5% of the titanium-coated reinforcing phase nanoparticles.

3. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 1, characterized in that: The titanium alloy powder includes one or more combinations of pure titanium, TC4, TA11 and TA15, and the particle size of the titanium alloy powder ranges from 15 to 53 μm.

4. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 1, characterized in that: In the step 1, the vacuum drying treatment is as follows: placing the titanium alloy powder and the titanium-coated reinforcement phase nanoparticles in stainless steel trays respectively, and keeping them in a vacuum environment at 100 to 120° C. for 1 to 2 hours; In the ball milling process, a grinding ball with a diameter of 5 mm was selected, the ball-to-material ratio was 1:2, the ball mill speed was 100-200 rpm, the ball milling time was 4-8 h, and the ball milling atmosphere was an argon atmosphere.

5. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 1, characterized in that: In step 2, the vacuum drying temperature is 100-120° C. and is kept warm for 3-5 hours.

6. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 1, characterized in that: The additive manufacturing equipment is a selective laser melting equipment, and argon gas is introduced into the selective laser melting equipment to fill the printing chamber to keep the oxygen content in the printing chamber below 100 ppm, and the formed substrate is a TC4 substrate; The process parameters of the selective laser melting equipment are: laser spot diameter is 80μm, laser power is 100-300W, scanning speed is 300-1000mm / s, scanning spacing is 50-100μm, powder layer thickness is 20-60μm, and forming substrate preheating temperature is 160-200℃.

7. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 1, characterized in that: In step 1, the method for preparing the titanium-coated reinforcing phase nanoparticles comprises the following steps: Step a. ball-milling titanium powder and reinforcing phase particles to obtain a uniform mixed powder, wherein the particle size of the titanium powder is 20 to 200 μm, the particle size of the reinforcing phase particles is 10 to 100 μm, the mass fraction of the titanium powder in the mixed powder is 15 to 50%, and the rest is reinforcing phase particles; Step b. preparing the mixed powder into titanium-coated reinforcement phase powder by high-frequency induction plasma method; Step c. Screening titanium-coated reinforcing phase powder with a particle size of less than 1 μm as titanium-coated reinforcing phase nanoparticles.

8. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 7, characterized in that: The reinforcing phase particles include one or more combinations of B powder, LaB6 and B4C.

9. The method for preparing a high-performance titanium-based composite material based on additive manufacturing according to claim 7, characterized in that: In step b, the preparation of titanium-coated reinforcement phase powder by high-frequency induction plasma method is carried out in a vacuum reaction chamber, and an inert gas is filled in the vacuum reaction chamber so that the air pressure value of the vacuum reaction chamber is between 0.01 and 0.03 MPa, and the mixed powder is sent into the vacuum reaction chamber at a speed of 3 to 20 m / s under the action of the inert gas.

10. A high-performance titanium-based composite material based on additive manufacturing, characterized in that: The high-performance titanium-based composite material is a high-performance titanium-based composite material prepared by the method for preparing a high-performance titanium-based composite material based on additive manufacturing as described in any one of claims 1 to 9.

Citation Information

Cited By

  • Post-treatment method for high-toughness modification of molten titanium-based composite material of laser powder bed

    CN120533116A

  • A post-processing method for high strength and toughness modification of laser powder bed fused titanium-based composite materials

    CN120533116B

  • Resistance thermal additive manufacturing method and device for large-size nano nickel component

    CN120920743A

  • Preparation method of high-toughness nickel-based alloy composite powder for additive manufacturing

    CN121104090A

  • Method for preparing B4C / Ti6Al4V composite material through laser melting deposition and application of B4C / Ti6Al4V composite material

    CN121104115A